The Application of Hydrotherapy (Soaking Feet in Warm Water) Against Pain Reduction in Ny J's Clients with Hypertension - Mutmainah, Iin; Adi Nugroho, Setiyo; Munir, Zainal (Research of Service Administration Health and Sains Healthys, 2024)
Currently, hypertension is considered a global public health problem in the last few decades. Hypertension causes the heart muscle to thicken (hypertrophy) and results in its function as a pump being disrupted and its contractions reduced. Apart from that, it also causes damage to blood vessels in the brain, eyes (retinopathy) and/or kidneys (kidney failure). The initial symptoms that often appear in people with hypertension are headaches, usually in the nape and neck. Headaches are caused by increased blood pressure resulting in a decrease in oxygen to the brain which results in anaerobic metabolism and produces lactic acid and ultimately stimulates pain stimuli. There are many efforts that can be made to reduce hypertension, one of which is non-pharmacological in the form of Hydrotherapy (Warm Water Foot Soak) intervention. The aim of this research is to determine the effectiveness of the Application of Hydrotherapy (Warm Water Foot Soak) in Reducing Pain in Nursing Care with Hypertension Cases. Using a qualitative descriptive method in the form of a study cases using a research approach in the form of the nursing care process. The results obtained after implementing Hydrotherapy (Warm Water Foot Soak) for 3 x 24 hours, the client's pain complaints decreased, the client's high blood pressure decreased and the client looked calm. The conclusion based on the case evaluation was that Hydrotherapy (Warm Water Foot Soak) was effective for use as a nursing care intervention for hypertension sufferers.